Trends and pattern of diseases under integrated disease surveillance project in Jodhpur, Rajasthan: A retrospective observational study - Jayshree Shekhawat; Deepak Kumar; Pankaj Bhardwaj; Durga S Meena; Mahendra Kumar Garg (Wolters Kluwer Medknow Publications, 2023)
Background: Progress of the Integrated Disease Surveillance (IDSP) is of utmost importance to ensure optimal performance in Jodhpur, Rajasthan, India. The purpose of the study was to document the physical performance of the surveillance system on its core and support functions. Material and Methods: Mixed method study was conducted between September 2020 to October 2020. Quantitative data was collected from the district IDSP unit of the Chief Medical and Health Office (CMHO) for various blocks of Rajasthan using syndromic, presumptive, and laboratory-confirmed reporting formats. Ethical clearance was obtained from the Institutional Ethical Committee of AIIMS, Jodhpur. Results: Rajasthan reported outbreaks between 0.55 to 1.2% of the national average between 2015-2019. Acute respiratory infections, fever of unknown origin, and acute diarrhea were the leading diseases under the presumptive reporting format. Major syndromic cases reported were cough with/without fever (more than three weeks) and fever less than seven days with the rash. Laboratory-confirmed Dengue, Malaria, and hepatitis were reported more in urban Jodhpur. Conclusion: Despite some pitfalls, IDSP has made satisfactory improvements in its core and support functions in the Jodhpur district of Rajasthan. The number of preventable morbidity and mortality cases associated with notifiable infectious diseases in our country can be effectively countered by strengthening the IDSP reporting system.